Identification of supplier partnership critical success factors in the construction industry - Fatimah, Mahmud; Sharifah Nora Fadiani, Syed Abu Bakar (Universiti Malaysia Pahang, 2024)
In the construction industry, supplier partnerships and collaboration are crucial for overcoming competing objectives and fostering growth. Challenges such as interpersonal conflicts, lack of trust, unequal risk sharing, overdependence, cultural barriers, inefficient problem-solving, communication breakdowns, insufficient effort to sustain long-term cooperation, inadequate training, and exclusion can disrupt these partnership and hinder project progress. Thus, this paper aims to investigate the critical success factor (CSF) of supplier partnerships in the construction industry. The survey-based study was conducted using purposive sampling among top management in construction companies, resulting a final sample of 190 respondents. The study highlights the importance of trust, mutual commitment, and effective dispute resolution in shaping key relationship traits linked to successful supplier partnerships in the construction industry. The findings on CSFs in supplier partnerships provide valuable insights for construction practitioners, helping them prevent disputes, improve partnership efficiency, and eliminate adversarial interactions.